2021
DOI: 10.1021/acsomega.1c02563
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-Integrated Sensors toward Rapid Detection of Single Nucleotide Variations

Abstract: Rapid detection of single nucleotide variations (SNVs) is of critical importance to early diagnosis of several diseases and the prediction of diverse responses to a specific treatment. Based on the information published in the literature, discrimination of SNVs is a developing area of study with great research enthusiasm and is also an area that can benefit from microfluidics-integrated designs. This review provides a brief overview of different microfluidics-based strategies for rapid detection of SNVs and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… 136 , 137 Systems integrating sensors measuring mechanical forces, nucleotide variations, and small molecule release have also been reported. 138 140 In turn, one can begin to realize the utility for a microchip with dynamic force control, particularly in the context of studying traumatic brain injury. Approaches to modeling traumatic brain injury in human mini brain models often include needle-stick injury, sheer injury via a moving plate, or even high intensity focused ultrasound (HIFU) induced mechanical injury, all of which have their own caveats.…”
Section: Organ-on-a-chip: Utilizing Microfluidics For Cns Modelingmentioning
confidence: 99%
“… 136 , 137 Systems integrating sensors measuring mechanical forces, nucleotide variations, and small molecule release have also been reported. 138 140 In turn, one can begin to realize the utility for a microchip with dynamic force control, particularly in the context of studying traumatic brain injury. Approaches to modeling traumatic brain injury in human mini brain models often include needle-stick injury, sheer injury via a moving plate, or even high intensity focused ultrasound (HIFU) induced mechanical injury, all of which have their own caveats.…”
Section: Organ-on-a-chip: Utilizing Microfluidics For Cns Modelingmentioning
confidence: 99%
“…[ 1–6 ] Genome‐wide association studies have identified SNVs associated with diverse human illnesses, such as cancer, neurodegenerative disease, cardiovascular disease, genetic disease, and predisposition to diseases. [ 6–11 ] To enable on‐time decisions for patient care and increase the diagnostic capacity, rapid SNV detection is crucial not only for disease diagnosis and personalized medicine but also for pathogenesis studies and efficient epidemic prevention and control. [ 1,9,12 ] SNVs may influence the transmissibility of pathogens and the degree of immunity produced by natural infection, as some mutant sites can enhance infectivity, increase virulence, and cause immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic systems such as lab-on-a-chip and micro-total analysis systems (μTAS) [1][2][3] play an essential role in biomedical applications such as point-of-care diagnostics, 4) drug discoveries, 5) and viral detection, 3) because of their cost effective abilities; e.g. for separations, 6,7) cell analysis, 8) and particle synthesis.…”
Section: Introductionmentioning
confidence: 99%